Matriconditioning Improves Thermotolerance in Pepper Seeds through Increased in 1-Aminocyclopropane-1-Carboxylic Acid Synthesis and Utilization - SATRIYAS ILYAS (Bogor Agricultural University, Indonesia, 2006)
Matriconditioning using a solid carrier, Micro-Cel E, was applied on pepper seeds and its effects on the improvement of thermotolerance through the ethylene biosynthesis were studied. Untreated and matriconditioned seeds were soaked in 5 mM 1-aminocyclopropane-1-carboxylic acid (ACC) for various time at 25 oC to studies the time course of ACC-derived ethylene production. To study the performance of the seeds at high temperature, they were planted at temperature regime of 35 oC, 12h light/27 oC, 12h dark. The ACC-oxidase activity of the seeds after incubated in ACC at 35 oC was also determined. The ACC contents in untreated and matriconditioned seeds during the 24h imbibition period at 35 oC were monitored. No ethylene was detected during soaking of pepper seeds in the absence of ACC. In 5 mM ACC detectable levels of ethylene were produced; the matriconditioned seeds producing 10-fold larger amounts than the untreated seeds at the time of germination. It is postulated that matriconditioning greatly increases the ACC-oxidase activity at the time of germination. Matriconditioned seeds imbibed at 35 oC produced larger amounts of ACC and greater ACC-oxidase activity than the untreated seeds. Thus, the basis for the thermotolerance by matriconditioned seeds may be increasing ability to synthesize ACC and to utilize it for ethylene production and stress alleviation. Key words: ACC-derived ethylene production, ACC-oxidase, germination, preplant conditioning